ILLEGAL MIGRATION OF JEWISH REFUGEES FROM POLAND TO THE AMERICAN OCCUPATION ZONE IN EUROPE IN 1945 – 1948 - YUSHKEVYCH, Volodymyr (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to analyze the causes, dynamics, and consequences of the illegal migration of the Jewish refugees from Poland to the American occupation zone in Europe in 1945 – 1948, highlighting its political, social, and geopolitical implications. The research methodology is based on the principles of a concrete historical approach – historicism, objectivity, comprehensiveness, integrity and systematicity, as well as on the methods of analysis and synthesis, historical and comparative, problem-chronological methods. The scientific novelty of this research consists in its detailed analysis of how the illegal migration of the Jewish refugees from Poland to the American occupation zone shaped and was influenced by the U.S. policy during the post-war period. By analyzing archival materials and declassified intelligence reports, in the study there have been highlighted the strategic and humanitarian dimensions of American responses, including the interplay between refugee management, geopolitical interests, and the evolving stance on Palestine. This research provides new insights into how the U.S. policy adaptations to migration crises reflected broader objectives, revealing the intersection of domestic priorities and international diplomacy in the mid-20th century. Conclusions. The illegal migration of the Jewish refugees from Poland to the American occupation zone in Europe in 1945 – 1948 was a complex and multifaceted phenomenon shaped by the interplay of political, social, and economic factors. Key drivers included anti-Semitism, economic instability, and widespread disillusionment with the post-war political order, but the movement's motives and organization remain subjects of debate. While some migration was spontaneous, others suspected coordinated efforts by Zionist organizations or external actors, which prompted the U.S. authorities to launch investigations into the causes, motives, and nature of these flows. American intelligence agencies and counterintelligence units played a critical role, uncovering both humanitarian and political dimensions of the migration, as well as alleged collusion between certain organizations and the Soviet authorities. In response, the U.S. government implemented specific measures, including the establishment of separate refugee camps, diplomatic negotiations with Allied powers, and policy adjustments to address the influx. Simultaneously, the issue of Jewish refugees intersected with the geopolitical future of Palestine, where their plight became a critical factor in the U.S. and British deliberations on the establishment of the Jewish state. The migration crisis not only underscored the urgency of resolving the Palestinian issue but also demonstrated how displaced people became a catalyst for broader shifts in international policy. Thus, this study contributes to a deeper understanding of post-war migration processes, the political and humanitarian strategies they inspired, and their enduring impact on global geopolitics. Keywords: U.S. refugee policy, illegal migration, Jewish refugees, post-war Europe, American occupation zone, displaced people, Palestine issue.